1999
DOI: 10.1021/bi990220t
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Association and Phosphorylation of IκB Isoforms by IκB Kinase 2 Correlate with Their Cellular Regulation in Human Endothelial Cells

Abstract: Activation of the transcription factor NF-kappaB depends on the specific dual phosphorylation of its inhibitor protein IkappaB by the homologous cytokine-inducible IkappaB kinases 1 and 2 (IKK1/2). Various IkappaB isoforms exist: IkappaBalpha, IkappaBbeta1/2 (two alternative splice variants), and IkappaBepsilon. However, the individual relevance and the specific regulation of these isoforms is not well-understood. We have studied the direct interaction of recombinant IkappaBalpha, IkappaBbeta1, IkappaBbeta2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Previous reports indicate that the kinetics of IκBβ degradation is unique and slower than that of IκBα following LPS stimulation (Thompson et al, 1995). Additionally, IKK is known to have a lower affinity for IκBβ when compared to IκBα (Heilker et al, 1999;Mercurio et al, 1997). It is possible that at lower doses, both parthenolide and BAY 11-7085 inhibit IKK activity enough to prevent phosphorylation of proteins that interact with IKK with lower affinity, including IκBβ.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicate that the kinetics of IκBβ degradation is unique and slower than that of IκBα following LPS stimulation (Thompson et al, 1995). Additionally, IKK is known to have a lower affinity for IκBβ when compared to IκBα (Heilker et al, 1999;Mercurio et al, 1997). It is possible that at lower doses, both parthenolide and BAY 11-7085 inhibit IKK activity enough to prevent phosphorylation of proteins that interact with IKK with lower affinity, including IκBβ.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical models and experimental data indicated that NF-kB dynamics are sensitive to the timing and duration of the IKK activity (Cheong et al 2008). Indeed, the affinity between IKK and the different IkBs correlates with their degradation rate, implicating IKK as the main factor that shapes the differential kinetics (Heilker et al 1999).…”
Section: Degradation Kinetics Of the Different Ikbsmentioning
confidence: 99%
“…The IKK activity has been isolated and characterized from mammalian cells as well as from expression of recombinant IKK1 and IKK2 homodimers in baculovirus systems (9,12,15,(23)(24)(25)(26)(27). Both the isolated IKK complex from mammalian cells and the recombinant IKKs utilize all three isoforms of IBs, ␣, ␤, and ␥, as substrates equally well.…”
Section: Nuclear Factor Kappa B (Nf-b)mentioning
confidence: 99%